The Effect Of Causal Factors And Coping Strategies On Academic Burnout Among Students Of The Faculty Of Economics And Business, Universitas Negeri Jakarta - Khairunnisah (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
The high academic pressure experienced by students, such as excessive workload, lack of social support from the surrounding environment, and an unsupportive learning environment, can trigger emotional exhaustion, cynicism, and a decline in achievement in an individual. These issues form the background of this study, which uses a quantitative approach with a survey method and involves 65 respondents selected through purposive sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics software. The results indicate that the factors causing academic burnout have a significant influence on students’ academic burnout, with workload being the most dominant factor. Meanwhile, coping strategies do not show a statistically significant influence on students’ academic burnout levels. These findings indicate that although students employ various coping strategies, their impact on reducing burnout levels remains low. Therefore, preventive efforts are needed to manage academic workload and strengthen social support from the university. This study contributes to understanding students’ psychological conditions and can serve as a basis for the government and higher education institutions to design more student-centered educational policies that prioritize mental health.